2023
DOI: 10.1161/hypertensionaha.122.20756
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Antihypertensive Drugs of Different Classes After Renal Denervation in Spontaneously Hypertensive Rats

Abstract: Background: Renal denervation (RDN) lowers blood pressure (BP) in patients with uncontrolled hypertension. Limited data exist on the effectiveness of different antihypertensive medications following RDN on BP and maladaptive cardiac phenotypes. Methods: Eighty-nine male spontaneously hypertensive rats with continuous BP recording underwent RDN or sham operation. Ten days postsurgery, spontaneously hypertensive rats were randomized to receive no antihype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Identifying likely responders in advance may improve the cost-effectiveness of the procedure. RDN has been demonstrated in previous research to reduce renin levels [ 17 19 ], and our team's studies indicate that hypertensive patients with high renin levels have better treatment outcomes when taking RDN [ 20 ]. As a result of this 10-year follow-up study, it has also been confirmed that RDN is more effective at lowering BP in hypertensive patients with a high renin level, providing strong evidence for the selection of RDN indications in the future.…”
Section: Discussionmentioning
confidence: 95%
“…Identifying likely responders in advance may improve the cost-effectiveness of the procedure. RDN has been demonstrated in previous research to reduce renin levels [ 17 19 ], and our team's studies indicate that hypertensive patients with high renin levels have better treatment outcomes when taking RDN [ 20 ]. As a result of this 10-year follow-up study, it has also been confirmed that RDN is more effective at lowering BP in hypertensive patients with a high renin level, providing strong evidence for the selection of RDN indications in the future.…”
Section: Discussionmentioning
confidence: 95%